Family Support in Caring for Elderly People with Hypertension in Pacekulon Village Pace District, Nganjuk Regency (HEALTH CARE: JURNAL KESEHATAN, 2024)
Introduction: Family support for hypertensive patients is the family's attitudes, actions and acceptance of hypertensive elderly. Support can improve healing and compliance with therapy at home, including instrumental, assessment, informational and emotional support. The aim of the research is to determine family support in caring for elderly people with hypertension in Pacekulon Village, Pace District, Nganjuk Regency. Method: Retrospective descriptive research design, the population is all families who have elderly people with hypertension in Pacekulon Village totaling 132 families, a sample of 40 respondents using a purposive sampling technique. The research was carried out on 23 March 2023 – 03 April 2023, the research variable was family support in caring for elderly people with hypertension, the research instrument used a questionnaire, the data was analyzed using a percentage formula and interpreted quantitatively. Results: Of the 40 respondents, almost all of them, namely 24 respondents (60%) had good family support, almost half of the respondents, namely 12 respondents (30%) had sufficient family support and a small portion of respondents, namely 4 respondents (10%) had poor family support. Factors that influence family support are age, gender, education, relationship with family, average monthly income, length of illness. Conclusions and Suggestions: Good family support accelerates the patient's recovery process. Health workers are expected to provide counseling regarding family support at posyandu for the elderly to increase the family's insight into family support for the elderly.